PENGARUH EKSTRAK KULIT PISANG AMBON (MUSA PARADISIACA L) TERHADAP JUMLAH SEL INFLAMASI PADA TIKUS PERIODONTITIS - Orienty, Fauzia Nilam; Lestari, Citra; Andriani, Ika (Universitas Baiturrahmah, 2023)
Introduction: Periodontitis is a chronic infection of periodontal tissues caused by interplay between periodontopatogen bacterial and the immune system. In periodontitis condition, inflammatory cells are found in large numbers and will release proinflammatory cytokines. Non-steroidal anti-inflammatory (NSAID) is one of a class of drugs used in periodontitis cases treatment. However, long treatment using NSAIDs may give side effects such as gastrointestinal disorder. Ambon banana peel (Musa paradisiaca L),a medicinal plant contains flavanoid, alkonoid, tanin and saponin which has anti-inflammatory effect due to its ability in inhibiting inflammatory cell migration. This research aimed to study the effect of the Ambon banana peel extract as an antiinflammation on the number of inflammatory cells infiltration in the periodontitis induced rats. Methods : This research uses experimental laboratory with Post Test Only Control Group Design. Silk ligature was placed in subgingival areas at the lower anterior teeth of male Wistar rats for 14 days to induce periodontitis. After 14 days, the ligation was released and the rats from each group were administered orally either with 25%, 50% concentrations extract and aquades (control negative). The rats were then decapitated 1, 5 and 7 days after the treatment.The serially sections were stained with hematoxylin eosin to examine the number of inflammatory cell infiltration. Results :Two-way Anova showed significant differences (p <0.05) among groups, indicating that Ambon banana peel extract affected the number of neutrofil cells infiltration. Conclusion: There is an effect of Ambon banana peel (Musa paradisiaca L) extract to reduce inflammatory cells infiltration.